The Tourism Promotion Strategy Key Factors: Comparative Study (Algeria, Morocco and Tunisia) - Krim, Yasmine; Lalaoui, Khaled (القطب الجامعي بالقليعة - مدرسة الدراسات العليا التجارية, 2021)
يضطلع قطاع السياحة في معظم الدول تقريبا بدور المحرك للتنمية المستدامة والداعم للنمو الاقتصادي. ومن ضمن هذه الدول، يمكن التنويه بالجزائر كمثال من حيث غنى وتنوع مقوماتها الطبيعية والثقافية والتاريخية التي تجعل منها وجهة سياحية متميزة. وعلى الرغم من ذلك، فإن الجزائر لم تتمكن في 2018، من استقطاب إلا 2 مليون سائح مقارنة بالمغرب وتونس اللتين تمكنتا على التوالي، من استقبال 11و 8 مليون سائح. سنقوم في هذا المقال بدراسة تحليلية لاستراتيجية الجزائر في مجال السياحة وعرض رؤية تسويقية للنهوض بها، بالإضافة إلى استعراض أهم عوامل النجاح الذي حققته المغرب وتونس في نفس المجال. In almost every country, the tourism sector works as the engine of sustainable development and support for the economic growth. Amongst these countries, Algeria could be given as an example with its rich and diversified natural, cultural and historical assets, which makes it a privileged tourist destination. Nevertheless, only 02 million tourists visited Algeria in 2018, compared to Morocco and Tunisia, which both received, respectively 11 and 8 million tourists. In this article, we are going to analyze the Algerian tourism strategy and submit a marketing vision for its promotion, as well as review the key factors of the success achieved in Morocco and Tunisia in the same area.
Keywords: التنمية المستدامة -- النمو الاقتصادي -- المقومات الطبيعية